Model Komunikasi Organisasi Badan Kemakmuran Masjid dalam Meningkatkan Pengelolaan Masjid di Kota Subulusssalam - Candra; Rubino; Muniruddin (PERSPEKTIF, 2023)
The research aims to determine the organizational communication model of the mosque welfare agency in improving mosque management in Subulussalam City. This type of research is descriptive qualitative research using a field research design to obtain an in-depth description of the data. Data obtained through interviews, document studies, and observation. Purposive interview of the Prosperity Board of the Great Mosque, Assilmi and Taqwa in the City of Subulussalam. Non-participant observation to obtain data from activities inside and outside the mosque as far as they are observed. Meanwhile, document studies are used to discover the history, vision and mission, BKM structure, and the main work programs of the three mosques studied. The results of the study show that: 1) The organizational communication model of the Mosque Prosperity Agency in improving the management of mosques in the city of Subulussalam generally uses an interpersonal communication model, namely the process of exchanging information between one person and another can be directly known, because within us alone there are communication components such as source, message, channel receiver and feedback; 2) The communication media for the organization of the mosque's prosperity agency, namely the delivery of information, which is carried out directly or indirectly. Direct communication media within the organization, namely the eyes and ears and indirect communication media that are carried out using mobile media, WhastApp, Facebook, Messenger; 3) Organizational communication barriers of the mosque prosperity agency in managing the mosque are technical barriers, limited mosque facilities and equipment.